Pengaruh Beban Pajak, Profitabilitas, dan Perencanaan Pajak terhadap Manajemen Laba - Sari, Yesi Permata; Handayani, Desi; Djefris, Dedy (LP2M Politeknik Jambi, 2024)
Earnings management is management's effort to increase or decrease company profits by choosing accounting policies that can be used. This study aims to examine and analyze the effect of deferred tax expense, current tax expense, profitability and tax planning on earnings management. The research method used is a quantitative approach with secondary data obtained from the idx.co.id website. The population in this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX). The sampling technique was carried out by purposive sampling method with total sample of 27 companies. Data is processed using the SPSS v.26 application. The results show that partially deferred tax expense has a negative effect on earnings management, current tax burden has a positive effect on earnings management, profitability has no leffect on earnings management and tax planning has a positive effect on earnings management. Simultaneously deferred tax expense, current tax burden, profitability and tax planning affect earnings management. It is hoped that this research can be used by users of financial statement in making decisions.